Health Education and Therapeutic Group Therapy for Mental Emotional and Pornography Addiction in Adolescents in Coastal Areas - M. Akbar Nugraha; Fitriya Handayani; Nurman Hidaya; Darni Darni; Rahma Yulis (GLOBAL HEALTH SCIENCE GROUP, 2026)
Mental health issues in adolescents, such as anxiety and depression, are a significant and growing global public health problem. The combination of health education and group therapy offers an opportunity to increase adolescents' understanding of mental health, reduce stigma, sexual problems and enhance self-esteem through positive interpersonal experiences within a group. This study explores the combination of health education and therapeutic group therapy for adolescents in addressing mental-emotional problems and pornography addiction in coastal areas. The research design used was a quasi-experimental study with pre and post tests without a control group. The sample size for comparing two means, with a 99% confidence interval and 90% power, resulted in a total sample size of 20. The inclusion criteria were: residing in a coastal area, being willing to participate in the study by signing an informed consent form, and being able to communicate effectively. The study used four questionnaires as data collection tools: the SRQ-20 (Self-Reporting Questionnaire-20), the Rosenberg Self-Esteem (RSE) questionnaire, the loneliness level questionnaire, and the pornography addiction questionnaire. Univariate analysis using frequency distribution and bivariate analysis using the Wilcoxon test. Health education and therapeutic group therapy have an impact on emotional and mental problems, pornography addiction, and self-esteem. A combination of interventions, including Health education and therapeutic group therapy, may be recommended to strengthen protective factors in adolescents, particularly those in coastal areas.